1998
DOI: 10.1097/00005072-199810000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of JE (Monocyte Chemoattractant Protein-1) Is Induced by Sciatic Axotomy in Wild Type Rodents but Not in C57BL/Wld S Mice

Abstract: Recruitment of hematogenous myelomonocytic cells into injured peripheral nerve is essential for axonal regeneration. The monocyte chemoattractant protein-1 (JE) and melanoma growth stimulatory activity/gro (KC) "immediate early" gene products may be important in this process as these proteins are potent chemoattractants for macrophages and neutrophils, respectively. To test this hypothesis, we examined JE and KC activation in rat sciatic nerve 0-30 days after surgical transection. RT-PCR and in situ hybridizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 0 publications
7
35
0
Order By: Relevance
“…For this experiment, mice were killed at 1.5 and 24 h after lesion. These two time points were selected based on a previous study, which showed that MCP-1 mRNA is already expressed at 1.5 h after sciatic nerve lesion, with maximal expression occurring at 24 h (Carroll and Frohnert, 1998). As expected, we found no hybridization signal for any of the proinflammatory molecules analyzed (i.e., IL-1␤, MCP-1, TNF, IFN␤, and iNOS) on sciatic nerve sections obtained from noninjured mice.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…For this experiment, mice were killed at 1.5 and 24 h after lesion. These two time points were selected based on a previous study, which showed that MCP-1 mRNA is already expressed at 1.5 h after sciatic nerve lesion, with maximal expression occurring at 24 h (Carroll and Frohnert, 1998). As expected, we found no hybridization signal for any of the proinflammatory molecules analyzed (i.e., IL-1␤, MCP-1, TNF, IFN␤, and iNOS) on sciatic nerve sections obtained from noninjured mice.…”
Section: Resultssupporting
confidence: 51%
“…However, the fact that MCP-1 expression precedes the appearance of axonal and myelin debris in the injured PNS [the first signs of axonal fragmentation distal to the lesion are typically seen after 36 -44 h after injury (Beirowski et al, 2005)] does not support the possibility that necrotic cells are responsible for initiating innate immune responses during WD. Nevertheless, because MCP-1 expression is considerably delayed in peripheral nerves of Wld s mutant mice (Carroll and Frohnert, 1998), and because early cytokine expression after nerve injury can be blocked by pretreatment with a calpain inhibitor (calpain is known to disassemble cytoskeletal proteins after axonal damage) (Uceyler et al, 2007), it is tempting to speculate that the endogenous ligand(s) responsible for TLR activation is released by degenerating axons. In this regard, a study by Willis and Twiss (2006) has recently identified Ͼ100 distinct axonally synthesized proteins, including several HSPs, in lesioned dorsal root ganglion sensory axons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the differences we have found between decentralization and axotomy in the macrophage population of the SCG argues against such a systemic effect playing a major role in the macrophage population in the SCG. In addition, recent studies have demonstrated that monocyte chemoattractant protein (MCP-1) is increased within the SCG after axotomy (Schreiber et al, 1997;, as it is within the degenerating stump of the transected sciatic nerve (Carroll and Frohnert, 1998;Toews et al, 1998: Subang andRichardson, 2001). We are currently examining whether this peptide plays a necessary role in the infiltration of macrophages into the SCϪ/Ϫ, using MCP-1 null mutant mice.…”
Section: Discussionmentioning
confidence: 99%